Incidence and prevalence of psoriatic arthritis, ankylosing spondylitis, and reactive arthritis in the first descriptive population-based study in the Czech Republic - Hanova, P; Pavelka, K; Holcatova, I; Pikhart, H (Scandinavian journal of rheumatology, 2010)
OBJECTIVE: To estimate the annual incidence and prevalence of psoriatic arthritis (PsA), ankylosing spondylitis (AS), and reactive arthritis (ReA) in a sample of the Czech population. METHODS: The population-based study was conducted in two regions of the Czech Republic (with a total population of 186000 inhabitants) in 2002-2003. Incident cases were registered on condition of confirming a definite diagnosis according to existing classification criteria during the study period (1 March 2002 to 1 March 2003). Prevalence was studied on the basis of identification of established diagnoses (before 1 March 2002) from registers of living patients of participating rheumatologists and other specialists. The age-standardized estimates of incidence and prevalence were calculated using the European standard population. RESULTS: The total annual incidence of PsA in adults aged >or= 16 years was 3.6/100000 [95% confidence interval (CI) 1.4-7.6/100000] and the prevalence of PsA was 49.1/100000 (95% CI 39.5-60.4/100000). The annual incidence of AS in adults was 6.4/100000 (95% CI 3.3-11.3/100000) and the prevalence of AS was 94.2/100000 (95% CI 80.8-109.2/100 000). The annual incidence of ReA in adults was 9.3/100000 (95% CI 5.5-14.8/100000) and the prevalence of ReA was 91.3/100000 (95% CI 78.1-106.2/100000). CONCLUSION: The annual incidence and prevalence rates of PsA, AS, and ReA in the first population-based survey in the Czech Republic compared well with data reported from other countries.
Keywords: Arthritis, Reactive; senioři; psoriatická artritida; Prevalence; prohibitiny; senioři nad 80 let; Age Distribution; Incidence; Arthritis, Psoriatic; mladiství; Česká republika; Prohibitins; Middle Aged; mužské pohlaví; prevalence; incidence; Adult; Czech Republic; ankylózující spondylitida; reaktivní artritida; Aged, 80 and over; ženské pohlaví; Spondylitis, Ankylosing; Humans; věkové rozložení; lidé středního věku; zdravotnické přehledy; dospělí; Female; Aged; Adolescent; lidé; Male; Health Surveys